Social Networks and Health in a Prison Unit. (September 2018) - Haynie, Dana L.; Whichard, Corey; Kreager, Derek A.; Schaefer, David R.; Wakefield, Sara
Although a growing body of research documents lasting health consequences of incarceration, little is known about how confinement affects inmates' health while incarcerated. In this study, we examine the role of peer social integration and prisoners' self-reported health behaviors (smoking, exercise, perception of health, and depression) in a prison unit. We also consider whether inmates with similar health characteristics cluster within the unit. Drawing on a sample of 132 inmates in a "good behavior" unit, we leverage social network data to ask: In prison, is it healthier to become friends with other prisoners or keep your head down and "do your own time"? Using exponential random graph models and community detection methods, findings indicate that social integration is associated with better health outcomes. However, race-ethnicity, religious identity, and exercise intensity emerge as key factors sorting inmates into social groups and likely shaping the distribution of health behaviors observed in the unit.